Studies on Megachile Latreille subgenus Callomegachile Michener (Hymenoptera: Megachilidae) from Chandigarh and Haryana plains, India - Kumari, Priyanka; Kumar, Neelima R. (Zootaxa, 2014)
Floral associations of three species of Megachile (Callomegachile) from NW India are provided: M. (C.) disjuncta, M. (C.) cephalotes and M. (C.) lerma. Morphological characters of both sexes and the male genitalia of each species are presented and illustrated. All three species are new records for Union Territory (Chandigarh) and Haryana in India.